Quality assurance and quality improvement to enhance yield in the process of dental education. Issue 12 (23rd November 2021) - Chambers, David W.
Abstract : Issue: The second paper in this three‐part perspective on improving dental education through focus on outcomes explores the two common ways of controlling variance in processes such as dental education. Approach: Quality assurance is based on the view that variance is a characteristic of the material or product produced by the process. In the case of dental education this means students. The reputation of educational programs depends to some extent on identifying and correcting or putting aside output that do match standards. This is an expensive process that does not improve educational programs. Quality improvement, by contrast, is grounded in the assumption that there is unwanted variation in the process itself. Impact: Reducing system variation through judicious adjustment at each cycle of the process raises yield, reduces the proportion of defects, and reduces program cost. Examples are given where good decisions in the reflection stage of the GEAR cycle make goals more realistic, improve experiences, and promote more effective assessment.